2022
DOI: 10.3389/fphar.2022.842636
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in Non-alcoholic Fatty Liver Disease

Abstract: Non alcoholic steatohepatitis (NASH) is the inflammatory reaction of the liver to excessive accumulation of lipids in the hepatocytes. NASH can progress to cirrhosis and hepatocellular carcinoma (HCC). Fatty liver is the hepatic manifestation of metabolic syndrome. A subclinical inflammatory state is present in patients with metabolic alterations like insulin resistance, type-2 diabetes, obesity, hyperlipidemia, and hypertension. Platelets participate in immune cells recruitment and cytokines-induced liver dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 198 publications
(234 reference statements)
0
8
0
Order By: Relevance
“…As a result of activation and adhesion, platelets release a variety of cellular mediators from their granule cargo, including TGF, PDGF-B, CXCL4, vWF, and platelet-derived S1P which stimulates HSC to increase collagen secretion, proliferation, migration, and transformation into myofibroblasts [ 75 ]. Animal studies have demonstrated that S1P activates and proliferates HSCs, while the accumulation of platelets and platelet-derived chemokine CXCL4 in fibrotic areas in chronic liver disease patients supports in vitro findings that platelet-derived CXCL4 induces HSC proliferation and chemotaxis [ 65 , 69 ].…”
Section: The Roles Of Platelets In Masldmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of activation and adhesion, platelets release a variety of cellular mediators from their granule cargo, including TGF, PDGF-B, CXCL4, vWF, and platelet-derived S1P which stimulates HSC to increase collagen secretion, proliferation, migration, and transformation into myofibroblasts [ 75 ]. Animal studies have demonstrated that S1P activates and proliferates HSCs, while the accumulation of platelets and platelet-derived chemokine CXCL4 in fibrotic areas in chronic liver disease patients supports in vitro findings that platelet-derived CXCL4 induces HSC proliferation and chemotaxis [ 65 , 69 ].…”
Section: The Roles Of Platelets In Masldmentioning
confidence: 99%
“…High glucose concentrations are also associated with mitochondrial dysfunction and platelet damage, as well as mitochondrial membrane potential dissipation and caspase-3 activation, which lead to apoptosis in subsets of platelets [ 136 ]. Platelet hyper-reactivity in MASLD patients can also be determined by the activated coagulation cascade that favors thrombin production, which not only cleaves fibrinogen into fibrin but also represents the most potent platelet activator via proteinase-activated receptor (PAR) 1-4 signaling [ 75 ]. This observation is supported by a murine study showing that the use of thrombin inhibition with dabigatran in a mouse model with a high-fat diet can attenuate body weight gain and reduce hepatic fibrin deposition, inflammation, and hepatocyte injury, thus limiting MASLD progression [ 137 ].…”
Section: Coagulation Disturbances In Masldmentioning
confidence: 99%
“…For instance, Poothong and colleagues demonstrated that ER stress can be activated by increased FVIII expression, which ends with amyloid-like fibrils; a process that might be reversed through the restoration of glucose metabolism [ 182 ]. In NAFLD, the coagulation cascade leads to thrombin production after being activated by the VWF and plasminogen activator inhibitor type I (PAI-1), which stimulate platelet hyperactivity mediated by the proteinase activated receptor 1–4 (PAR1–4) [ 183 ]. A correlation between PAI-1, endoplasmic reticulum stress, and NAFLD progression to NASH was previously shown in murine models of NAFLD/NASH [ 184 , 185 ].…”
Section: Possible Interaction Mechanisms Among Coagulation Dyshomeost...mentioning
confidence: 99%
“… [2] , [3] , [4] , [5] Although macrophages and T cells have been extensively studied in NAFLD, the role of platelets in NASH development has gained recognition. [6] , [7] , [8] , [9] , [10] In addition to their well-known role in regulating blood hemostasis, accumulating evidence suggests that platelets are significant contributors to NAFLD/NASH. [6] , [7] , [8] , [9] , [10] Previous studies have reported an association between the platelet count and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“… [6] , [7] , [8] , [9] , [10] In addition to their well-known role in regulating blood hemostasis, accumulating evidence suggests that platelets are significant contributors to NAFLD/NASH. [6] , [7] , [8] , [9] , [10] Previous studies have reported an association between the platelet count and NAFLD. [11] , [12] , [13] , [14] Furthermore, studies using rodent models have demonstrated that anti-platelet therapy can alleviate NASH development 6 and reduce liver damage in patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%